INALL exchange visit between Senegal, Burkina Faso and Tunisia - Sib, Ollo; Piraux, Marc; Rudiger, Udo; Fall, Modou Gueye; Sene, Mame Birame (2024)
Objectives of the exchange visit were: Facilitate exchanges among Burkina Faso, Senegal, and Tunisia stakeholders on opportunities and challenges related to forage production, milk value chains, and small-scale mechanization. Enable Burkina Faso and Tunisia stakeholders to visit the Senegalese Agroecological Living Landscape (ALL) in Fatick and share experiences on ALL governance and facilitation practices. Foster collaboration by bringing together scientists and stakeholders from the three countries to meet with the DyTAES (Dynamic for Agroecological Transition in Senegal).